Effectiveness of Positive Thinking Skills on Improving the Situation of Fathering Behavior, Conversation and Anger in Relation of Daughters and their Veteran Fathers - M. Mallahi; F. Niknejadi (Afarand Scholarly Publishing Institute, 2017)
Aims: To the parents and adolescents, the adolescence period is full of stressful situations. The children of the veterans undergoing mental pressures due their veteran fathers' emotional avoidance continuously during all their mental improvement stages, their quality of life decreases. The aim of the study was to investigate the effectiveness of the positive-thinking skills on the improvement of paternal engagement, dialogue, and anger in the adolescent female children of the veterans' families.   Materials & Methods: In the controlled pretest-posttest experimental study, 30 female high-school students of the veterans' families in Isfahan were studied in the academic year 2015-16. The subjects, selected via cluster random sampling method, were randomly divided into two groups including experimental (n=15 persons) and control (n=15 persons) groups. Data was collected by the parent-child survey (the father form). Eight positive-thinking skills training sessions were conducted in experimental group, while control group received no training. Data was analyzed by SPSS 16 software using one-variable analysis of covariance test. Findings: At the posttest stage, the mean scores of the groups were significantly different including the relationship components (dialogue), paternal engagement, and anger (p<0.05). Nevertheless, the groups were not significantly different in the positive emotion component (p>0.05). Then, through the pretest effects control, the positive skills trainings improved paternal engagement, relationships, and anger in the girls, excepting the positive emotion.  Conclusion: The positive-thinking skills trainings can improve the paternal engagement, dialogue, and anger in the female students of the veterans' families. Such trainings can also enhance their mental health quality.